Consumer perceptions of the application of edible coatings on fresh beef (Research, Society and Development, 2022)
This study aimed to evaluate the consumers’ perception about using of edible coating (EC) in fresh beef as a preservation technology and the influence on the purchase and consumption habits of this product. An online questionnaire was used, which was posted on social medial in the national territory and answered voluntarily. 423 responses were evaluated, mostly female (72.8%), aged between 18 and 35 years (70.9%), single (61.9%), high education levels (87.8%) and monthly family income from two to four minimum wages (25.1%). Most respondents purchase food for their homes (61.2%), prefer to do in supermarkets (62.2%), consider the odor and appearance of fresh beef the most important attributes for their acquisition (64.8% and 64.4%, respectively) and consume the fresh beef two to four times a week (47.8%). The respondents are familiar with EC (34.7%), consider that technology very important for foods and that information about EC is present on the label (96%). About the application of EC in beef, the participants consider this practice to be very interesting for the conservation (51.1%), but they are curious to know the product to have your own opinion (73.2%). Thus, we conclude that consumers believe that the application of EC may have a great potential for preserving fresh beef.